COMPOSIÇÃO CENTESIMAL, COMPOSTOS BIOATIVOS E PARÂMETROS FÍSICO-QUÍMICOS DO JENIPAPO (GENIPA AMERICANA L.) IN NATURA - Paula Pacheco; Josiane Gonçalves da Paz; Cassiano Oliveira da Silva; Grazieli Benedetti Pascoal (Universidade do Estado do Rio de Janeiro, 2015)
Introduction: Cerrado is a diversified biome which has many types of fruit species, among which the Genipapo (Genipa americana L.) stands out. Objective: To analyze the centesimal composition, bioactive compounds and physicochemical parameters in in natura (fresh) Genipapo. Methodology: Genipapo was bought in shops located in the Brazilian states of Minas Gerais and Goiás. The analyses were performed in triplicate and the results were expressed as mean and standard deviation. Moisture, proteins, lipids, ashes, dietary fiber, vitamin C, titratable acidity, soluble solids and pH were determined following the methods of the Association of Official Analytical Chemists and Adolfo Lutz Institute. In addition, analyses of "available" carbohydrates were performed by the phenol-sulfuric method and by difference; the levels of beta-Carotene were analyzed by spectrophotometry. Antioxidant activity was performed by the DPPH assay. Results: The Genipapo pulp showed 70.0% moisture; 0.5% protein; 0% lipids; 1.1% ashes; 6.3% dietary fiber; 20.1% "available" carbohydrates; 22.1% "available" carbohydrates (by difference); 26.0 mg vitamin C/100 g; 0 mg beta-Carotene/100 g; 176.3 mg of phenolic compounds/100 g; pH 3.85; 15.2 ºBrix total soluble solids (TSS); 0.40% titratable acidity and 70.2% antioxidant capacity. Conclusion: The in natura Genipapo showed considerable values for moisture, total carbohydrates (mainly dietary fiber), vitamin C, phenolic compounds, acidity, soluble solids and high antioxidant activity. Thus, its inclusion in the diet could improve quality, contributing to food and nutritional security of the Cerrado population. DOI: http://dx.doi.org/10.12957/demetra.2014.11310